MANAGEMENT OF VASCULAR WILT OF LENTIL THROUGH AQUEOUS PLANT EXTRACTS IN TARAI REGION OF UTTARAKHAND STATE - GARKOTI, ANKITA; KUMAR , VIJAY; H. S. TRIPATHI (The Bioscan, 2013)
Lentil wilt caused by Fusarium oxysporum Schechet. Emend. Snyder and Hansen f. sp. lentis Vasudeva and Srinivasan is an important disease and it is a limiting factor to lentil production. The present work aimed at evaluating the antifungal activity of some plant extracts in vitro and in vivo condition. Field experiments were conducted at N. E. Borlaug Crop Research Centre of G. B. Pant University of Agriculture and Technology, Pantnagar. Field trials were carried out consecutively during Rabi 2010-11 and 2011-12 crop seasons in Randomized Block Design (RBD) with three replications, using ‘Pant L-639’ a released cultivar to wilt. The plot size was 3.0×1.5m2 with row spacing of 30cm. On the basis of in vitro studies, effective plant extracts were used for seed treatment. Effect of selected plant extracts on disease incidence, 1000 grain weight and yield of lentil was recorded. All the botanicals were observed effective. However, garlic extract seed treatment followed by ginger, showed lowest disease incidence, highest grain yield as well as maximum 1000-grains weight in comparison to check plot. The reduction in the pathogen population/ growth, decreased disease incidence and increased grain yield indicates that these extracts could have important roles in biologically based management strategies for control of Fusarium wilt disease under organic mode of lentil cultivation.